Evaluation of Information Security Risks of E-Learning Systems: A Case Study on UUM Learning Zone - Tan, Wai Beng (2011)
This project is conducted with the purpose of identifying security risks associated with E-Learning Systems in UUM Learning Zone by using OCTAVE Allegro. To narrow down the scope of the project, Computer Centre staffs from Universiti Utara Malaysia (UUM) are targeted. The information security risks of E-Learning Systems will be predicted and classified based on OCTAVE Allegro approach by focusing primarily on information assets in the context of how they are used, where they are stored, transported and processed and how they are exposed to threats, vulnerabilities and disruptions as a result. This project will show the OCTAVE Allegro approach which consists of eight steps that are organized into four phases. Detail descriptions of the OCTAVE Allegro methodology applied is also included in the report. The findings of the project such as highlighting the possible security risks are expected to provide UUM’s Computer Centre management an in-depth view on the information security risks in UUM Learning Zone.